Reinterpreting Gender Equality: An Analysis of Hadiths in Sahih al-Bukhari and Sahih Muslim - Fauziah, Sarah; Kosasih, Engkos; Wiwaha, Rizzaldy Satria (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to explore the normative potential of hadiths in Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim in strengthening gender equality within Islam. The research is motivated by the persistence of patriarchal interpretations that often marginalize women from public life, thereby necessitating a more just and contextual reinterpretation. Employing a qualitative design through library research, the study examines hadith texts alongside classical and contemporary scholarly interpretations. Data analysis follows Miles and Huberman’s framework of reduction, display, and conclusion drawing. The findings identify six major themes on gender: prohibition of gender impersonation, the Prophet’s  exhortation to treat women kindly, the virtue of raising daughters, prioritizing mothers over fathers, the ethics of patience in marital relations, and the Prophet’s  role model in domestic life, education, and leadership. Classical interpretations emphasize moral and spiritual dimensions, while contemporary scholars extend the discourse toward social-political equality and patriarchal deconstruction. The study’s implications highlight hadith as a normative basis for advancing gender equality in education, family, and leadership within contemporary Muslim societies. The originality of this research lies in its integration of hadith analysis with modern gender theories (Judith Butler, Amina Wadud, and maqāṣid al-sharī‘ah), offering a novel framework for Islamic and gender studies.